Aspergillus galactomannan detection in exhaled breath condensate compared to bronchoalveolar lavage fluid for the diagnosis of invasive aspergillosis in immunocompromised patients. (June 2018) - Bhimji, A.; Bhaskaran, A.; Singer, L.G.; Kumar, D.; Humar, A.; Pavan, R.; Lipton, J.; Kuruvilla, J.; Schuh, A.; Yee, K.; Minden, M.D.; Schimmer, A.; et al.
Abstract: Objectives: Exhaled breath condensate (EBC) is a noninvasive means of sampling the airways that has shown significant promise in the diagnosis of many disorders. There have been no reports of its usefulness in the detection of galactomannan (GM), a component of the cell wall of Aspergillus. The suitability of EBC for the detection of GM for the diagnosis of invasive aspergillosis (IA) using the Platelia Aspergillus enzyme-linked immunosorbent assay was investigated. Methods: Prospective, cross-sectional study of lung transplant recipient and haemotologic malignancy patients at a university centre. EBC samples were compared to concomitant bronchoalveolar lavage (BAL) samples among lung transplant recipients and healthy controls. EBC was collected over 10 minutes using a refrigerated condenser according to the European Respiratory Society/American Thoracic Society recommendations, with the BAL performed immediately thereafter. Results: A total of 476 EBC specimens with 444 matched BAL specimens collected from lung transplant recipients ( n = 197) or haemotologic malignancy patients ( n = 133) were examined. Both diluted and untreated EBC optical density (OD) values (0.0830, interquartile range (IQR) 0.0680–0.1040; and 0.1130, IQR 0.0940–0.1383), respectively, from all patients regardless of clinical syndrome were significantly higher than OD values in healthy control EBCs (0.0508, IQR 0.0597–0.0652; p < 0.0001). However, the OD index values did not correlate with the diagnosis of IA (44 samples were associated with IA). Furthermore, no significant correlation was found between EBC GM and the matched BAL specimen. Conclusions: GM is detectable in EBC; however, no correlation between OD index values and IA was noted in lung transplant recipients.